Filozofka i paso doble - Malitowska, Anna (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2021)
The subject of the book is ballroom dancing, understood as an artistic-cultural practice. The author outlines the problem context, in which dance as a cultural phenomenon is not a common subject of research, especially in Poland. As for ballroom dance – it is of even less interest to academia. Its artistry seems unnoticed by art in general, while its culture-forming dimension is marginalized in education. This “cultural absence” clearly contrasts with the growing popularity of ballroom dancing as a competitive sport, or form of mass entertainment provided by television programs such as “Dancing with the Stars”. Starting from such a diagnosis, the author demonstrates that ballroom dance extends beyond its sporting, utilitarian or consumerist dimensions and is becoming a self-conscious artistic practice that affects social and cultural discourses. The book consists of three essays, each of them presenting a different theoretical perspective on ballroom dancing. The first essay, exploring the field of choreography, examines how composition, which transforms gestures and figures into routines, is nourished by cultural traditions. The understanding and interpretation of dance are addressed in the second essay, which develops a “dance audience” concept, building on hermeneutics and cultural semiotics. In the third essay, the author presents ballroom dancing as a historical discourse of art and discusses the role of cultural competencies in dance-art creation, understanding, appraisal, and alteration. The argument made in the book is illustrated with references to the choreographies and achievements of leading ballroom couples, and is supported by findings in the fields of critical cultural studies, philology, literature studies, linguistics and semiotics, and art history, as well as research on visual culture and performance art.
Tematem książki jest taniec towarzyski rozumiany jako artystyczna praktyka kulturowa. Autorka zarysowuje kontekst problemowy, w którym taniec jako zjawisko kulturowe nie jest częstym, zwłaszcza w Polsce, przedmiotem badań. Jeszcze rzadziej obiektem naukowego zainteresowania okazuje się taniec towarzyski. Artyzm tej formy tańca i jego potencjał kulturotwórczy są marginalizowane także w życiu artystycznym i na polu edukacyjnym. Kontrastuje z tym coraz większa popularność tańca jako rywalizacji sportowej i jako masowej rozrywki, zapewnianej przez programy telewizyjne typu Taniec z Gwiazdami. Diagnozując powyższy stan rzeczy, Autorka wykazuje, w jaki sposób taniec towarzyski wykracza poza sportowy, użytkowy i konsumpcyjny charakter, i staje się samoświadomą praktyką artystyczną, odziaływującą na życie społeczne i proces kulturowy. Książka zawiera trzy eseje, które stanowią zarazem trzy perspektywy refleksji teoretycznej nad tańcem. W szkicu pierwszym, w perspektywie choreograficzno-kompozycyjnej, podjęte zostaje zagadnienie tworzenia choreografii. Zadając pytanie, na czym polega rozumienie i interpretowanie tańca jako obiektu posiadającego własności semiotyczne – w szkicu drugim Autorka rozwija perspektywę odbiorcy dzieła tanecznego. W trzecim eseju, w którym omówiona zostaje perspektywa procesu historyczno-choreologicznego, Autorka dokonuje rekonstrukcji tańca jako dyskursu sztuki i objaśnia, jakie kompetencje kulturowe biorą udział w procesie tworzenia, odbioru i wartościowania tańca jako praktyki artystycznej. Argumentacja została omówiona na przykładzie choreograficznych dokonań par tańca towarzyskiego oraz poparta ustaleniami badawczymi z zakresu krytycznych studiów kulturowych, filologii i teorii literatury, teorii języka, historii sztuki, badań nad kulturą wizualną i sztukami performatywnymi.
Keywords: ballroom dancing; dance criticism; art of dance; choreography; performance art; taniec towarzyski; krytyka tańca; sztuka taneczna; choreografia; sztuka performatywna